Psychosocial Factors Predict Pain and Physical Health After Lower Extremity Trauma. Issue 11 (November 2015) - Archer, Kristin R.; Abraham, Christine M.; Obremskey, William T.
Abstract: Background: There has been increasing evidence to support the importance of psychosocial factors to poor outcomes after trauma. However, little is known about the contribution of pain catastrophizing and fear of movement to persistent pain and disability. Questions/purposes: Therefore, we aimed to determine whether (1) high pain catastrophizing scores are independently associated with pain intensity or pain interference; (2) high fear of movement scores are independently associated with decreased physical health; and (3) depressive symptoms are independently associated with pain intensity, pain interference, or physical health at 1 year after accounting for patient characteristics of age and education. Methods: Of 207 eligible patients, we prospectively enrolled 134 patients admitted to a Level I trauma center for surgical treatment of a fracture to the lower extremity. Sixty percent of patients (80 of 134) had an isolated lower extremity injury and the remainder sustained additional minor injury to the head/spine, abdomen/thorax, or upper extremity. Pain catastrophizing was measured with the Pain Catastrophizing Scale, fear of movement with the Tampa Scale for Kinesiophobia, and depressive symptoms with the Patient Health Questionnaire. Pain and physical health outcomes were assessed with the Brief Pain Inventory and the SF‐12, respectively. Assessments were completed at 4 weeks and 1 year after hospitalization. Multiple variable hierarchical linear regression analyses were used to address study hypotheses. One hundred ten patients (82%) completed the 1‐year followup. Results: Pain catastrophizing at 4 weeks was associated with pain intensity (β = 0.67; p < 0.001) and pain interference (β = 0.38; p = 0.03) at 1 year. No association was found between fear of movement and physical health (β = 0.15; p = 0.34). Depressive symptoms at 4 weeks were associated with pain intensity (β = 0.49; p < 0.001), pain interference (β = 0.51; p < 0.001), and physical health (β = −0.32; p = 0.01) at 1 year. Conclusions: Catastrophizing behavior patterns and depressive symptoms are associated with more severe pain and worse function after traumatic lower extremity injury. Cognitive and behavioral strategies that have proven effective for chronic pain populations may be beneficial for trauma patients. Future research is needed to determine whether the early identification and treatment of subgroups of at‐risk patients based on catastrophizing behavior or depressive symptoms can improve long‐term outcomes. Level of Evidence: Level I, prognostic study.